2015
DOI: 10.1093/infdis/jiv126
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Vector, Single-Injection Trivalent Filovirus Vaccine: Proof of Concept Study in Outbred Guinea Pigs

Abstract: The filoviruses, Marburg marburgvirus (MARV), Zaire ebolavirus (ZEBOV), and Sudan ebolavirus (SEBOV), cause severe and often fatal hemorrhagic fever in humans and nonhuman primates (NHPs). Monovalent recombinant vesicular stomatitis virus (rVSV)-based vaccine vectors, which encode a filovirus glycoprotein (GP) in place of the VSV glycoprotein, have shown 100% efficacy against homologous filovirus challenge in rodent and NHP studies. Here, we examined the utility of a single-vector, single-injection trivalent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
1
23
1
2
Order By: Relevance
“…Thus, our studies provide no evidence that an EBOV GP immunogen lacking NGSs on GP1 elicits novel protective immune responses to highly conserved regions of GP on the surfaces of extracellular SUDV particles. To date, the most effective broad-spectrum protection has been achieved through combinatorial vaccines that present proteins from multiple viral species to the host (11,39,44,(65)(66)(67). Taking this together with our results, a mixture of VSVΔG pseudotyped with representative GPs from the filovirus family could provide an efficient, tractable, and safe vaccine that warrants further investigation in other animal model systems.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, our studies provide no evidence that an EBOV GP immunogen lacking NGSs on GP1 elicits novel protective immune responses to highly conserved regions of GP on the surfaces of extracellular SUDV particles. To date, the most effective broad-spectrum protection has been achieved through combinatorial vaccines that present proteins from multiple viral species to the host (11,39,44,(65)(66)(67). Taking this together with our results, a mixture of VSVΔG pseudotyped with representative GPs from the filovirus family could provide an efficient, tractable, and safe vaccine that warrants further investigation in other animal model systems.…”
Section: Discussionsupporting
confidence: 54%
“…With recent observation that sequential immunization with rVSV-based LASV and EBOV vaccines does not alter their overall protective efficacy against both targets, rVSV platform is well suited to control both infections in West Africa. In addition, rVSV vector expressing glycoproteins of three filoviruses, ZEBOV, SEBOV, and MARV from three separate open reading frames was designed and successfully tested in challenge experiments in guinea pigs [138]. All these observations indicate that rVSV platform can be used to express LASV GPC from different clades and develop pan-LASV vaccine.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 96%
“…Past studies showed that AG129 (alpha/beta interferon [IFN-␣/␤CFR R Ϫ/Ϫ ) mice are susceptible to wild-type SUDV infections (12) and that an adapted SUDV was partially lethal to approximately 25% of guinea pigs (13). A more stringent intermediate animal model is needed to screen candidate drugs more effectively before progression to studies in NHPs.…”
mentioning
confidence: 99%